Sessile Serrated Adenomas in Young Patients may have Limited Risk of Malignant Progression. Issue 3 (March 2019) - Bettington, Mark; Brown, Ian; Rosty, Christophe; Walker, Neal; Liu, Cheng; Croese, John; Rahman, Tony; Pearson, Sally-Ann; McKeone, Diane; Leggett, Barbara; Whitehall, Vicki
Abstract : Goals: To provide preliminary evidence that sessile serrated adenomas (SSA) are low-risk polyps in young patients. Background: SSAs are the dominant polyp of the serrated neoplasia pathway and as such are the precursor of up to 20% of colorectal carcinomas (CRC). Up to 90% of these cancers are expected to harbor a BRAF mutation. SSAs are being diagnosed with increasing frequency in young patients, placing a significant burden on colonoscopic services. Evidence to direct the surveillance intervals for these young patients is not available. Study: We utilized 2 patient cohorts comprising (1) a consecutive series of patients who underwent outpatient colonoscopy through a tertiary hospital and (2) a consecutive series of resection specimens for CRC processed through a gastrointestinal pathology service. The prevalence of SSAs by age was determined in the patients undergoing colonoscopy and compared with the ages of patients with BRAF mutated CRC in the pathology series. Results: The prevalence of SSAs was similar irrespective of age. By comparison, BRAF mutated CRCs were very rare (3.8% of cases) in patients younger than 50 years of age and uncommon (9.3% of cases) in patients younger than 60 years of age, but increased to 39.8% in patients older than 80 years of age. Conclusions: These results suggest that SSAs develop at a young age, but have a prolonged dwell time and are unlikely to develop into cancer in patients younger than 60 years of age. These findings highlight the need for further targeted research to determine the most appropriate surveillance intervals for young patients with sporadic SSAs.